2020
DOI: 10.3390/toxins12060394
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin Paves the Way for the Treatment of Functional Lower Urinary Tract Dysfunction

Abstract: Botulinum toxin A (BoNT-A) is a potent protein that can selectively modulate neurotransmission from nerve endings, resulting in the blocking of neurotransmitter releases and causing muscular paralysis [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Yu et al demonstrated that the level of malondialdehyde (MDA), a marker of oxidative stress which indicates the rate of lipid peroxidation, was considerably reduced in spinal cord injury-induced mice model treated with BoNT along with minocycline, indicating reduced oxidative stress [ 65 ]. Further, many studies have suggested the use of therapeutic BoNT-A in urinary bladder dysfunctions resulting from prostatic hyperplasia due to its positive effect in controlling oxidative stress [ 66 , 67 ]. Very recently, Yesudhas et al reported that BoNT improves the enzymatic activities of key antioxidants and provides neuroprotection in the brain of ageing experimental animals [ 11 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al demonstrated that the level of malondialdehyde (MDA), a marker of oxidative stress which indicates the rate of lipid peroxidation, was considerably reduced in spinal cord injury-induced mice model treated with BoNT along with minocycline, indicating reduced oxidative stress [ 65 ]. Further, many studies have suggested the use of therapeutic BoNT-A in urinary bladder dysfunctions resulting from prostatic hyperplasia due to its positive effect in controlling oxidative stress [ 66 , 67 ]. Very recently, Yesudhas et al reported that BoNT improves the enzymatic activities of key antioxidants and provides neuroprotection in the brain of ageing experimental animals [ 11 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several issues are difficult to treat using medication or surgery. Because Botox has an anti-inflammatory mechanism of action, LUTDs related to chronic inflammation might be treated with Botox injection at the target organ or afferent nerves to achieve a satisfactory result [ 148 ]. In patients with chronic SCI, AD is a challenge for urological management, and Botox injection might reduce AD severity and improve the quality of life of these patients.…”
Section: Potential Clinical Applications Of Botox On Recurrent Uti De...mentioning
confidence: 99%